Freedom of Movement - Drakokhrust, Tetiana (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
Freedom of movement is a fundamental right enshrined in Article 2 of Protocol No. 4 of the European Convention on Human Rights (ECHR). This right guarantees individual the liberty to move within the borders of a state, to leave any country, and to return to their country of origin. However, the right to freedom of movement is not absolute and can be subject to restrictions. These restrictions must be prescribed by law, necessary in a democratic society, and pursued for legitimate aims such as national security, public safety, public order, prevention of crime, or protection of health, morals, or the rights of others. The European Court of Human Rights (ECtHR) plays a crucial role in interpreting and enforcing this right, balancing individual freedoms with state interests. The Court has developed a substantial body of case law that delineates the scope and limitations of freedom of movement, considering factors such as proportionality and necessity of the restrictions imposed by states. The Court’s jurisprudence also highlights the importance of the right in the context of migration, residency rights, and the treatment of non-citizens, emphasizing the protection of individuals against arbitrary or discriminatory restrictions. The chapter provides an overview of the legal framework, key principles, and significant case law under the ECHR concerning freedom of movement, offering insights into how this right is protected and limited within the European human rights system. Keywords: Freedom of movement, European Convention on Human Rights, Article 2 Protocol 4, European Court of Human Rights, restrictions